Collaborative Governance in the Development of Ecotourism Based on Local Wisdom in Biak Numfor Regency - Edyanto, Edyanto; Asmadianto, Asmadianto; Iriawan, Hermanu (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
The concept of collaborative governance can be used in the development of ecotourism as a solution to overcome the welfare problems of indigenous Papuans and strengthen local cultural identity. The purpose of this study is to analyze (1) collaborative governance in the development of ecotourism based on local wisdom in Biak Numfor Regency, (2) Supporting and inhibiting factors in the development of ecotourism based on local wisdom in Biak Numfor Regency, (3) How is the recommendation of the collaborative governance model in the development of ecotourism based on local wisdom in Biak Numfor Regency, (4) Recommendations for policy models in the development of ecotourism based on local wisdom in Biak Numfor Regency, (4) Recommendations for policy models in the development of ecotourism based on local wisdom in Biak Numfor Regency? Biak Numfor Regency that is effective and sustainable. The research method used in this study is qualitative, data collection techniques are carried out through observation, interviews, documentation, and focus group discussions. This study shows that the development of ecotourism based on local wisdom in Biak Numfor Regency has great potential because it is supported by local natural and cultural wealth and high awareness of indigenous peoples in protecting the environment through customary rules. However, this potential has not been balanced with effective governance, because management is still traditional, infrastructure is limited, human resource capacity is low, and local government budget support is minimal.